Study of the effect of the binder on the wear of locally manufactured grinding wheels - الرحيه مروه; سلامة أحمد; معلا هادي (Latakia University Journal -Engineering Sciences Series, 2023)
In this paper, the effect of resinous organic binders (Novolac, Novolac + Rezol, Rezol) on the wear properties of locally manufactured grinding wheels was studied. Where this wheels were manufactured using the used binders. The results of the tests showed an effect of the type of the binder, especially on the amount of weight loss. The best results were obtained in the grinding wheels manufactured using the resinous organic binder (Novolac + Rezol).